2020
DOI: 10.21921/jas.v6i02.18098
|View full text |Cite
|
Sign up to set email alerts
|

Site Specific Nutrient Management in Potato Through Nutrient Omission Plot Technique

Abstract: A field experiment was conducted during four consecutive winter seasons from 2013-14 to 2016-17 at Patna, Bihar under sandy clay loam soil. The trial on potato was laid out in randomized block design with four replications with objective to develop nutrient omission plot technique in potato. The highest plant height and number of shoot per plant were recorded under 150% recommended dose of fertilizer of NPK. The range of dry matter content in potato tuber varied from 16.1 to 17.7% on dry weight basis. The maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Whereas in low fertility area, site specific recommendation of fertilizer was higher than POP recommendation and higher growth parameters were observed under the treatment with site specific drip fertigation. This result clearly demonstrated that, irrigation and fertilizer levels have a significant impact on plant growth parameters in low fertility area [7]. By ensuring moisture and nutrient availability, fertigation is regarded to be one of the key aspects that result in increased plant growth [8].…”
Section: Growth Parametersmentioning
confidence: 79%
“…Whereas in low fertility area, site specific recommendation of fertilizer was higher than POP recommendation and higher growth parameters were observed under the treatment with site specific drip fertigation. This result clearly demonstrated that, irrigation and fertilizer levels have a significant impact on plant growth parameters in low fertility area [7]. By ensuring moisture and nutrient availability, fertigation is regarded to be one of the key aspects that result in increased plant growth [8].…”
Section: Growth Parametersmentioning
confidence: 79%
“…important short duration cash crop grown successfully Pdur ing winter season under Indo-Gangetic plains of India. The crop has been occupied a unique position among the vegetable crops due to its high nutritional value and protein quality as compared to that of cereals (Yadav et. al.…”
Section: Introductionmentioning
confidence: 99%
“…It is rich in vitamin C, B1, B2 and B6 and minerals such as potassium, phosphorous and magnesium and a good source of high-quality protein (Kahsay, 2019). It is short duration crop with high yield potential as compare to other crops and vegetables (Yadav et al, 2020). The important nutrients required for its cultivation are nitrogen, phosphorus and potassium applied at the recommended rate of 180:80:100 in the form of urea, diammonium phosphate or single super phosphate and murate of potash (Zewide et al, 2012).…”
Section: Introductionmentioning
confidence: 99%